Template free mild hydrothermal synthesis of core–shell Cu2O(Cu)@CuO visible light photocatalysts for N-acetyl-para-aminophenol degradation. Issue 36 (28th August 2019) - Karthikeyan, Sekar; Chuaicham, Chitiphon; Pawar, Radheshyam R.; Sasaki, Keiko; Li, Wei; Lee, Adam F.; Wilson, Karen
Abstract : Solar photocatalytic processes are a promising approach to environmental remediation, however their implementation requires improvements in visible light harvesting and conversion and a focus on low cost, Earth abundant materials. Abstract : Solar photocatalytic processes are a promising approach to environmental remediation, however their implementation requires improvements in visible light harvesting and conversion and a focus on low cost, Earth abundant materials. Semiconducting copper oxides are promising visible light photocatalysts for solar fuels and wastewater depollution. Here we report the mild, hydrothermal (template-free) synthesis of core–shell Cu2 O(Cu)@CuO photocatalytic architectures for the visible light photocatalytic degradation of N -acetyl- para -aminophenol (APAP). Hollow and rattle-like core–shell nanosphere aggregates with diameters between 200 nm and 2.5 μm formed under different synthesis conditions; all comprised an inner Cu2 O shell, formed of 10–50 nm nanoparticles, surrounded by a protective corona of CuO nanoparticles. High reductant and structure-directing agent concentrations promoted the formation of a yolk-like Cu2 O/Cu core, associated with improved photophysical properties, notably a high oxidation potential and suppressed charge carrier recombination, that correlated with the highest apparent quantum efficiency (8%) and rate of APAP removal (7 μmol g −1 min −1 ). Trapping experiments demonstrated hydroxyl radicals were the primary active species responsible for APAP oxidation to quinones and short chain carboxylic acids. Rattle-like core–shell Cu2 O/Cu@CuO nanospheres exhibited excellent physiochemical stability and recyclability for APAP photocatalytic degradation.